EXPRESSION OF CONCERN: Designing and Analysing an APP based on "Internet+" for Integrating Health Data of University Physical Classes - Zhang, Shuaishuai; Chen, Gang (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12702
Keywords: health data integration app; internet+; vulture search algorithm; convolutional neural network